Application of backward design in the implementation of curriculum management - Dano Ali, Yusuf Nugraha; Hernawan, Asep Herry (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
The curriculum is an educational experience that has been planned in a systematic and integrated manner where curriculum management is needed. It includes planning, organizing, implementing, and evaluating the curriculum applicable in management activities outside the classroom and the school in its application. The Backward Design model is also a form of curriculum that focuses on goals and identifying the expected results then moves backward to design activities aligned with predetermined outcomes. Seeing this, this study aims to explain the application of Backward Design in curriculum management. This must be described as a form of school preparation to guide students to achieve educational goals. The purpose of this study was to examine using scientific literature review methods to find data regarding flow and recommendation models that can be applied by schools related to the Backward Design curriculum model. The study's results suggest that this model can be carried out in-class learning and within the scope of curriculum management. It can also be carried out so that each step of curriculum management and its principles can be measured and carried out following predetermined goals. AbstrakKurikulum merupakan sebuah pengalaman pendidikan yang telah direncanakan secara sistematis dan terpadu dimana diperlukan sebuah manajemen kurikulum yang meliputi perencanaan, pengorganisasian, pelaksanaan dan evaluasi kurikulum dan dapat diaplikasikan dalam kegiatan pengelolaan di luar kelas serta di luar sekolah dalam pengaplikasiannya. Model Backward Design pun hadir sebagai sebuah salah satu bentuk kurikulum yang berfokus pada tujuan dan pengidentifikasian hasil yang diharapkan kemudian bergerak mundur untuk merancang kegiatan yang selaras dengan hasil yang telah ditentukan sebelumnya. Melihat hal tersebut, penelitian ini bertujuan untuk menjelaskan penerapan Backward Design dalam pengaplikasian manajemen kurikulum. Hal ini perlu dijelaskan sebagai bentuk persiapan sekolah membimbing peserta didik mencapai tujuan pendidikan Tujuan penelitian ini dikaji menggunakan metode kajian literatur ilmiah untuk mencari data mengenai alur dan model rekomendasi yang dapat diterapkan oleh sekolah terkait model kurikulum Backward Design. Hasil penelitian mengemukakan bahwa model ini tidak hanya dapat dilakukan secara khusus dalam pembelajaran di kelas tetapi juga dalam jangkauan yang lebih luas agar setiap langkah manajemen kurikulum serta prinsip nya dapat terukur dan dilakukan sesuai dengan tujuan yang telah ditentukan.Kata Kunci: Backward Design; Desain Kurikulum; Manajemen Kurikulum